Ulcerative colitis after SARS-CoV-2 infection - Sofia Kartsoli; Spyridon Vrakas; Dimitrios Kalomoiris; Kassiani Manoloudaki; Vasileios Xourgias (University of São Paulo, 2022)
Although severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) affects mainly the respiratory system, the gastrointestinal tract is also considered a site of viral activity. We hereby present the case of a 74-year-old male patient with the diagnosis of new-onset ulcerative colitis. One month earlier, the patient presented fever, running nose, and diarrhea and was tested positive for SARS-CoV-2. Studies with COVID-19 patients revealed significant changes in gut microbiota composition and alterations in immune responses that could lead to chronic inflammation and manifestations of inflammatory bowel disease. We review additional cases of ulcerative colitis presented after SARS-CoV-2 infection and summarize the possible mechanisms that underlie the gastrointestinal abnormalities in COVID-19 patients.